FOREIGN EXPERIENCE OF CORPORATE SOCIAL RESPONSIBILITY - Azarenkova, Galyna; Azarenkov, Serhii; Tarabanovskyi, Petro; Golovko, Olena; Kalinina, Kateryna (Socio-economic relations in the digital society, 2024)
In today’s dynamic business landscape, the concept of social responsibility has gained prominence, prompting enterprises to reassess their roles and responsibilities in society. This article undertakes a thorough examination of the definitions of social responsibility proposed by a multitude of authors and scholars. By synthesizing these perspectives, we aim to provide a nuanced understanding that guides enterprises in their pursuit of ethical, sustainable, and socially impactful practices. The primary objective is to comprehensively investigate the relationship between Corporate Social Responsibility (CSR) initiatives and business performance across various industries and geographic regions. Specifically, the article aims to achieve the following: • Analyze the Effectiveness of CSR Practices: The article seeks to assess the effectiveness of different CSR initiatives undertaken by businesses. • Measure Financial and Non-Financial Performance Metrics: The study will evaluate the impact of CSR initiatives on both financial performance indicators (e.g., revenue, profitability, stock performance) and non-financial metrics (e.g., brand reputation, customer loyalty, employee satisfaction). • Assess Stakeholder Perceptions and Expectations: Understanding the perspectives of key stakeholders, including consumers, investors, employees, and regulatory bodies, is crucial in evaluating the effectiveness of CSR initiatives. • Explore Industry and Regional Differences: Business environments vary significantly across industries and geographic regions, leading to diverse approaches to CSR adoption and implementation. • Identify Opportunities and Challenges: examine the challenges and limitations associated with CSR implementation. This article provides actionable insights for businesses to leverage CSR initiatives effectively. By aligning CSR practices with stakeholder expectations, leveraging industry insights, and addressing associated challenges, companies can foster sustainable business practices. This not only optimizes business performance but also contributes positively to society. Integrating CSR into corporate strategies emerges as imperative for driving long-term success and societal impact, highlighting the importance of responsible business practices in today’s dynamic landscape.